2017
DOI: 10.3340/jkns.2016.0809.003
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Balloon-Guiding Catheter for Mechanical Thrombectomy in Patients with Anterior Circulation Ischemic Stroke

Abstract: ObjectiveTo evaluate the efficacy of balloon guiding catheter (BGC) during thrombectomy in anterior circulation ischemic stroke.MethodsSixty-two patients with acute anterior circulation ischemic stroke were treated with thrombectomy using a Solitaire stent from 2011 to 2016. Patients were divided into the BGC group (n=24, 39%) and the non-BGC group (n=38, 61%). The number of retrievals, procedure time, thrombolysis in cerebral infarction (TICI) grade, presence of distal emboli, and clinical outcomes at 3 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 14 publications
1
27
2
Order By: Relevance
“…When comparing complications, distal embolization frequency was higher with BAO, but symptomatic hemorrhage occurred less in BAO than ACO. This increased incidence of distal embolization with BAO may be associated with a low application rate of BGC for BAO compared with ACO 17) . The use of BGC was limited due to the narrow diameter and tortuosity of the vertebra-basilar artery (17.5%), compared with anterior circulation (51.8%), therefore, distal embolization increased during mechanical thrombectomy of BAO than ACO.…”
Section: Discussionmentioning
confidence: 97%
“…When comparing complications, distal embolization frequency was higher with BAO, but symptomatic hemorrhage occurred less in BAO than ACO. This increased incidence of distal embolization with BAO may be associated with a low application rate of BGC for BAO compared with ACO 17) . The use of BGC was limited due to the narrow diameter and tortuosity of the vertebra-basilar artery (17.5%), compared with anterior circulation (51.8%), therefore, distal embolization increased during mechanical thrombectomy of BAO than ACO.…”
Section: Discussionmentioning
confidence: 97%
“…A Direct Aspiration J Korean Neurosurg Soc 63 (1) : [14][15][16][17][18][19][20][21][22][23][24][25] First Pass Technique (ADAPT) or contact aspiration thrombectomy (CAT) using large bore catheters is also employed as another frontline treatment for LVO 12,24,32) . During the evolution of thrombectomy strategies, the versatile uses of 8 F or 9 F balloon guide catheters (BGC) in different clinical setups have been recognized as BGCs can be paired with a single clot retriever system 23,48) or combined with other adjunctive thrombectomy procedures 15,37,39) .…”
Section: Introductionmentioning
confidence: 99%
“…[47][48][49][50][51][52][53] 2005 32. Lapergue B, Blanc R, Gory B, Labreuche J, Duhamel A, Marnat G, et al : Effect of endovascular contact aspiration vs stent retriever on revascularization in patients with acute ischemic stroke and large vessel occlusion: the ASTER randomized clinical trial.…”
mentioning
confidence: 99%
“…Certain studies have reported advantages of BGCs, such as prevention of thromboembolic complications, increased suction effectiveness, facilitation of clot removal, minimization of distal embolization and a shorter procedure time (7,(9)(10)(11). MT using BGCs has been indicated to facilitate improved clinical and radiological outcomes, compared with other techniques, via a reduction in both the number of stent passages' and incidence of distal emboli (10,12,13).…”
Section: Introductionmentioning
confidence: 99%